Displaying node-link structure with region of greater spacings and peripheral branches - John O. Lamping; Ramana B. Rao (1997)
Node-link data defining a node-link structure are used to present a sequence of representations on a display. The last representation in the sequence is perceptible as a changed continuation of the first. Each representation includes bounded node features, each with a center of area and a nearest node spacing that define a mid-spacing circle. All mid-spacing circles together determine an outer convex hull enclosing a total area for the representation. The mid-spacing circles of a subset of more spaced node features determine an inner convex hull enclosing approximately half the total area and enclosing a region in which nearest node spacings are in general perceptibly greater than in another region outside the second convex hull. The node features also represent a peripheral branch with lower level nodes that are not represented by more spaced node features. In the peripheral branch, node features that share a parent have centers of area positioned approximately along an arc with sufficiently similar spacings from the center of area of the parent node feature and from adjacent node features that they are perceptible as a group of related node features. The inner convex hulls of the first and last representations include subsets of node features representing different sets of nodes. The sequence can produce a perception that one node feature's nearest node spacing increases while another's decreases. The representations can be presented by a series of iterations, and can be presented at animation speeds to produce a perception of continuously moving node features.